Junior athletes’ nutritional demands: a narrative review of consumption and prevalence of eating disorders - Amawi, Adam; Khataybeh, Batool; Al Aqaili, Raghad; Ababneh, Nour; Alnimer, Lana; Qoqazeh, Ali; Oukal, Farah; Jahrami, Haitham; Mousa Ay, Khitam; Al Saoud, Hassan; Ghazzawi, Hadeel (Frontiers in Nutrition, 2024)
Information regarding the dietary requirements and consumption of young athletes is limited. Hence, the aim of this narrative review is to provide a comprehensive combination of research and review papers on the nutritional status of young athletes aged 5 to 18 years old, as well as quantitative, qualitative, wholesome foods, food choices, and eating disordered data concerning the dietary requirements for growing young athletes. This study involved systematic searches of electronic databases, including Google Scholar, PubMed, Science Direct, Scopus, and Web of Science. The specific criteria for identifying research papers published in English from July 1980 until May 2024 were included. Only 48 studies out of 1262 were included in this narrative review. The findings of this study suggest that, compared with adults, junior athletes need a unique approach to meet their dietary needs. Growth, development, and general athletic performance depend on macronutrients, as they are vital nutrients for young active athletes. However, research on enhancing junior athletes' performance is still in progress, and studies on hydration status, and eating disorders are limited.